Treatment outcomes of penetrating abdominal injury requiring laparotomy at Hiwot Fana Specialized University Hospital, Harar, Ethiopia - Abdulkadir, Adnan; Mohammed, Burka; Sertse, Elias; Mengesha, Melkamu Merid; Gebremichael, Mathewos Alemu (Frontiers in Surgery, 2022)
Background Penetrating abdominal injury (PAI) is a public health problem and accounts for significant mortality and disability in both developing and developed countries. It often causes damage to internal organs, resulting in shock and infection. In this study, we assessed the outcomes of PAI and factors associated with post-surgical outcomes including surgical site infection (SSI) and in-hospital death. Methods An institution-based cross-sectional study was conducted from 15 January to January 30, 2020, using a standard checklist to review the clinical charts of patients who presented to Hiwot Fana Specialized University Hospital (HFSUH) with PAI and underwent laparotomy between January 2015 and September 2019. Descriptive statistics were used to describe the characteristics of patients, and odds ratios (ORs) with a 95% confidence interval (CI) were reported for factors included in binary logistic regression. The statistical significance was declared at a P-value <0.05. Results A total of 352 charts of patients with PAI were reviewed. A majority of them (84.9%) were males and the mean age was 26.5 years. The anterior abdomen was the most common site of injury, accounting for 285 patients (81%), 329 patients (93.5%) suffered organ injury, 204 (62%) had a single organ injury, and 125 (38%) had more than one organ injury. The leading injured organs were small intestines 194 (55.1%), followed by the colon 88 (25%) and liver 40 (11.4%). The magnitude of SSI and hospital death was 84 (23.9%) and 12 (3.4%), respectively. Patients above 45 years of age (AOR = 2.9, 95% CI: 1.2, 9.2), with fluid collection (AOR = 2.7, 95% CI: 1.2, 5.9), colostomy (AOR = 3.9, 95% CI: 1.9, 7.8), body temperature >37.5 °C (AOR = 3.8,95% CI:1.9,7.6), and Hgb < 10 mg/dl (AOR = 7.4, 95% CI: 3.4,16.1) had a higher likelihood of SSI. Those patients admitted to the intensive care unit (AOR = 21.3, 95% CI: 1.1, 412.3) and who underwent damage control surgery (AOR = 9.6, 95% CI: 1.3, 73.3) had a higher likelihood of mortality. Conclusions SSI and death among patients with PAI were high. Age, fluid collection, colostomy, body temperature, and hemoglobin level were statistically associated with SSI, and intensive care unit and damage control surgery were statistically associated with death. Therefore, health professionals working in surgical wards should consider these factors to alleviate SSI and prevent death. Broadly speaking, the guidelines of the World Society of Emergency Surgery (WSES) should consider these factors in their recommendations.